Dabigatran etexilate for nonvalvular atrial fibrillation in real practice and promises for its use to prevent stroke - A.V. Fonyakin (Неврология, нейропсихиатрия, психосоматика)
The capabilities of antithrombotic therapy to prevent thromboembolic events in nonvalvular atrial fibrillation (AF) are substantially extended after designing and clinically introducing new oral anticoagulants, one of which is dabigatran. A wealth of world clinical experience with dabigatran has confirmed its efficacy and safety provided that all recommendations for dosage regimens are followed. The universal properties of the drug can hope that the indications for its use will be extended and will not be confined to the prevention and treatment of venous and atrial thromboses and thromboembolisms. Whether dabigatran may be used in acute myocardial infarction and coronary stenting in the presence of nonvalvular AF, left ventricular thrombosis, and cardiomyopathies is being considered today.